Relating diet, demographics and lifestyle to increasing US obesity rates - Christiane Schroeter (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2004)
Changes in the American lifestyle are putting more individuals at risk due to the declining quality of their diets. In the last 20 years, the readily available high-fat foods (e.g., "fast foods") combined with the decreased caloric requirements due to lower physical activity levels is assumed to be the major factor in the sharp rise in the prevalence of obesity. The typical away-from-home meal is less healthy than food at home, since it tends to contain more total fat and saturated fat, less calcium, fiber, and iron, and fewer servings of fruits and vegetables. Furthermore, due to the super-sizing trend that is sweeping the market, when Americans eat out, they eat more. Thus, a rising away-from-home consumption appears to establish a significant barrier to improve American dietary habits and health status. The continuously increasing trend towards obesity is affecting the public health system tremendously, since four of the ten leading causes of death in the US, including heart disease, cancer, stroke, and diabetes, are strongly associated with poor diet and physical inactivity. In terms of lost productivity and medical expenses, it leads to an estimated cost of dollar200 billion each year. Despite the considerable change in demographics and lifestyles, little research has documented the impact of changes in these factors on the rising US obesity. The objective of this study is to determine the impact of food source, diet, demographic, and lifestyle on the prevalence of obesity and overweight. This study will be based on data from the National Health and Nutrition Examination Survey (NHANES, 1999-2000), which, among many other variables, includes measured weight and height and hence provides the best opportunity to track trends in weight in the US NHANES, administered by the US Department of Health and Human Services. The NHANES provides nationally representative information on the health and nutritional status of the US population. While controlling for demographics, lifestyle and diet information, the main goal is to determine whether the source from which food is obtained also contributes to the increased overweight. Linear regression is applied to estimate the effect of food source, particularly fast-food outlets and restaurants, on the body mass index (BMI). BMI expressed as weight/height² (i.e. kg/m²), is commonly used to classify overweight (BMI: 25.0-29.9) and obesity (BMI: >= 30.0) among adults (age 18 years and over). Previous studies have found gender-specific differences in the effect of different factors on the BMI. This is tested empirically in this study. Quantifying the effects of demographic and lifestyle determinants on BMI will provide a better understanding of the impact of different factors on obesity.
Keywords: 330; Gesundheitsrisiko; Fast Food; Lebensstil; USA; Ernährungsverhalten